Purple urine bag syndrome- changing hue! - Sharma, Sadhna; Babu, Butchi; Rao, Bhaskar; Govind, Biju (International Journal of Research in Medical Sciences, 2017)
Purple Urine Bag Syndrome (PUBS) is a unique disease entity characterised by purple discoloration of urine secondary to recurrent urinary tract infections with indigo and indirubin producing bacteria and is predominantly seen in constipated, chronically debilitated and catheterised women with alkaline urine. This syndrome indicates underlying recurrent urinary tract infections (UTIs) associated with higher incidence of mortality and morbidity than urinary tract infection alone without this occurrence. This article is about an elderly hypothyroid woman with PUBS and reviews the need to be aware of this entity.